User-Centric Design Thinking Framework for Digital Transformation: Bridging the Digital Literacy Gap in Thai Manufacturing SMEs - Noamna, Somkeit; Kaewkamol, Porntida; Thanyaphongphat, Jirapipat (Journal of Applied Informatics and Technology, 2026)
While digital transformation is essential for enhancing the competitiveness of Small and Medium-sized Enterprises (SMEs), a significant barrier remains in the form of low levels of employees' digital literacy. This study addresses this critical challenge by proposing and validating a User-Centric Design Thinking Framework for developing digital tools in environments characterized by varying levels of technological proficiency. Using a Thai manufacturing SME as a case study, the study employed a five-stage Design Thinking process involving 20 participants to develop a web-based production management system. The methodology emphasized empathy and iterative feedback to ensure the system was intuitive, accessible, and aligned with user needs. Post-implementation analyses revealed substantial operational improvements, including an 81.1% reduction in production monitoring time and an 80.7% decrease in reporting time, accompanied by significant cost savings. Usability testing, incorporating both qualitative feedback and quantitative assessment, demonstrated a high level of user satisfaction (mean score = 4.52 out of 5). The findings indicate that a user-centric approach is effective in not only bridging the digital literacy gap but also enhancing business performance. This study provides a practical and replicable framework for technology adoption in SMEs and contributes to the broader understanding of inclusive digital transformation in developing economies.